2004
DOI: 10.1103/physrevb.69.085115
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic structure ofLaMnO3from hybrid periodic density-functional theory

Abstract: The electronic and magnetic structures of the LaMnO 3 compound have been studied by means of periodic calculations within the framework of spin polarized hybrid density-functional theory. In order to quantify the role of approximations to electronic exchange and correlation three different hybrid functionals have been used which mix nonlocal Fock and local Dirac-Slater exchange. Periodic Hartree-Fock results are also reported for comparative purposes. The A-antiferromagnetic ground state is properly predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
89
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 61 publications
9
89
0
Order By: Relevance
“…In this case, the manganese has valences (3+) and (4+), causing the existence of bonds of type Mn 3+ -Mn 3+ and Mn 3+ -Mn 4+ . This valence mixture is responsible for strengthening of effects such as colossal magnetoresistance (CMR) and the magnetocaloric effect (MCE) in manganites 6 . The La 1-x Ba x MnO 3 compounds have a high concentration of vacancies in both A (La/ Ba) and B (Mn) sites, which gives rise to large localized distortions, influencing the physical properties of the material [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the manganese has valences (3+) and (4+), causing the existence of bonds of type Mn 3+ -Mn 3+ and Mn 3+ -Mn 4+ . This valence mixture is responsible for strengthening of effects such as colossal magnetoresistance (CMR) and the magnetocaloric effect (MCE) in manganites 6 . The La 1-x Ba x MnO 3 compounds have a high concentration of vacancies in both A (La/ Ba) and B (Mn) sites, which gives rise to large localized distortions, influencing the physical properties of the material [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite-type RE 1-x AE x MnO 3 , with RE representing a rare earth and AE an alkaline earth ion (AE = Ca, Ba, Sr and Pb), has attracted great scientific interest because of its peculiar physical properties and potential technological applications such as magnetic recording, magnetic heating and switch control in hyperthermia treatment, refrigerating materials, and as a cathode in solid oxide fuel cells (SOFCs) [1][2][3][4][5][6] . Its fundamental properties show a strong correlation between crystal structure and chemical composition, and it displays features such as electronic transport and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the behavior of water on this surface ( 1 ML), we have used hybrid-exchange DFT calculations with the B3LYP functional, which result in an accurate description of the energetics and the electronic structure of periodic systems, [51][52][53][54][55][56][57][58][59][60][61][62][63][64] particularly for transition metal oxides, and, as implemented in the CRYSTAL code, are computationally efficient for large systems. 65 This approach aims to develop a detailed model of interactions for this surface, prior to uncovering the role of defects as well as dependence on surface facet: a thorough investigation of the energetics has been performed, and the method adopted facilitates the analysis of the interactions between adjacent adsorbates.…”
Section: Introductionmentioning
confidence: 99%
“…7-9. Recent studies have shown that hybrid exchangecorrelation functionals can accurately reproduce the basic bulk and surface properties of a number of ABO 3 perovskite materials, 10,11 including the low-temperature phase of LaMnO 3 ͑LMO͒. 12,13 We adopted here the hybrid B3LYP exchange-correlation functional within the density-functional theory ͑DFT͒, following Refs. 12 and 13.…”
mentioning
confidence: 99%